Perceptions of Price Unfairness: Antecedents and Consequences - Campbell, Margaret C. (Journal of Marketing Research, 1999)
Using two studies, the author examines the influence of the inferred motive for a firm's price increase on perceptions of price unfairness. Prior to the research presented here, the only established causal antecedent of perceived price unfairness was increased relative profit. In Study 1, the author extends the existing research by demonstrating that the inferred motive, as well as inferred relative profit, provides causal explanation of perceived price unfairness. When participants inferred that the firm had a negative motive for a price increase, the increase was perceived as significantly less fair than the same increase when participants inferred that the firm had a positive motive. In addition, the author shows in Study 2 that the firm's reputation can influence the inferred motive, thereby altering perceptions of price unfairness. Specifically, participants sometimes gave a firm with a good reputation the benefit of the doubt when inferring motive. If the “good” firm did not profit from the price increase, participants inferred significantly more positive motives than if it did profit. The firm with a poor reputation did not receive this benefit; inferred motive was equally negative regardless of whether the firm profited from the price increase. Together, these studies provide evidence that consumer inferences of the motive for a price increase influence the perceived fairness of the increase. Furthermore, reputation is shown to moderate the effect of inferred relative profit on inferred motive. Finally, analyses show that perceived unfairness leads to lower shopping intentions and demonstrate that perceived unfairness mediates the effects of inferred motive and relative price on consumers’ shopping intentions.